KAAACI Evidence-Based Clinical Practice Guidelines for Chronic Cough in Adults and Children in Korea - Song, Dae Jin; Song, Woo-Jung; Kwon, Jae-Woo; Kim, Gun-Woo; Kim, Mi-Ae; Kim, Mi-Yeong; Kim, Min-Hye; Kim, Sang-Ha; Kim, Sang-Heon; Kim, Sang Hyuck; Kim, Sun-Tae; Kim, Sae-Hoon; et al. (Allergy, asthma & immunology research, 2018)
Chronic cough is common in the community and causes significant morbidity. Several factors may underlie this problem, but comorbid conditions located at sensory nerve endings that regulate the cough reflex, including rhinitis, rhinosinusitis, asthma, eosinophilic bronchitis, and gastroesophageal reflux disease, are considered important. However, chronic cough is frequently non-specific and accompanied by not easily identifiable causes during the initial evaluation. Therefore, there are unmet needs for developing empirical treatment and practical diagnostic approaches that can be applied in primary clinics. Meanwhile, in referral clinics, a considerable proportion of adult patients with chronic cough are unexplained or refractory to conventional treatment. The present clinical practice guidelines aim to address major clinical questions regarding empirical treatment, practical diagnostic tools for non-specific chronic cough, and available therapeutic options for chronic wet cough in children and unexplained chronic cough in adults in Korea.